Comprehensive functional and anatomic assessment of myocardial bridging: Unlocking the Gordian Knot - Ciliberti, Giuseppe; Laborante, Renzo; Di Francesco, Marco; Restivo, Attilio; Rizzo, Gaetano; Galli, Mattia; Canonico, Francesco; Zito, Andrea; Princi, Giuseppe; Vergallo, Rocco; Leone, Antonio Maria; Burzotta, Francesco; et al. (Frontiers in Cardiovascular Medicine, 2022)
Myocardial bridging (MB) is the most frequent congenital coronary anomaly in which a segment of an epicardial coronary artery takes a tunneled course under a bridge of the myocardium. This segment is compressed during systole, resulting in the so-called “milking effect” at coronary angiography. As coronary blood flow occurs primarily during diastole, the clinical relevance of MB is heterogeneous, being usually considered an asymptomatic bystander. However, many studies have suggested its association with myocardial ischemia, anginal symptoms, and adverse cardiac events. The advent of contemporary non-invasive and invasive imaging modalities and the standardization of intracoronary functional assessment tools have remarkably improved our understanding of MB-related ischemia, suggesting the role of atherosclerotic lesions proximal to MB, vasomotor disorders and microvascular dysfunction as possible pathophysiological substrates. The aim of this review is to provide a contemporary overview of the pathophysiology and of the non-invasive and invasive assessment of MB, in the attempt to implement a case-by-case therapeutic approach according to the specific endotype of MB-related ischemia.